Citrus Limon L. Peel Powder Incorporated Polyvinyl Alcohol/Corn Starch Antioxidant Active Films - Terzioğlu, Pınar; Sıcak, Yusuf (Igdir University, 2021)
Active food packaging films has gain more significance over conventional packaging. In this study, novel active composite films were prepared by incorporating lemon peel to a polyvinyl alcohol-starch matrix. The morphological, thermal and antioxidant activity evaluation of polyvinyl alcohol-starch-lemon peel composite films were discussed to determine whether the presence and content of lemon peel influenced the film’s characteristics. The results indicated that tested properties of composite films depended on the content of lemon peel. It was found that the thermal stability and antioxidant activity of films considerably improved upon the incorporation of peel. The prepared films with enhanced antioxidant activity may be used for preservation of oxidation-sensitive food products. The results showed that lemon by-product has great potential to be evaluated into added-value products for functional packaging applications. The developed packaging films will be new alternatives for food preservation materials.

Active food packaging films has gain more significance over conventional packaging. In this study, novel active composite films were prepared by incorporating lemon peel to a polyvinyl alcohol-starch matrix. The morphological, thermal and antioxidant activity evaluation of polyvinyl alcohol-starch-lemon peel composite films were discussed to determine whether the presence and content of lemon peel influenced the film’s characteristics. The results indicated that tested properties of composite films depended on the content of lemon peel. It was found that the thermal stability and antioxidant activity of films considerably improved upon the incorporation of peel. The prepared films with enhanced antioxidant activity may be used for preservation of oxidation-sensitive food products. The results showed that lemon by-product has great potential to be evaluated into added-value products for functional packaging applications. The developed packaging films will be new alternatives for food preservation materials.
Citrus Limon L. Peel Powder Incorporated Polyvinyl Alcohol/Corn Starch Antioxidant Active Films
Keywords: Chemical Engineering; Kimya Mühendisliği [EN] Food Engineering; Gıda Mühendisliği